2023
DOI: 10.3390/cancers15092658
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of microRNAs in Hematologic Malignancies and Hematopoietic Stem Cell Transplantation

Abstract: Hematologic malignancies are a group of neoplastic conditions that can develop from any stage of the hematopoiesis cascade. Small non-coding microRNAs (miRNAs) play a crucial role in the post-transcriptional regulation of gene expression. Mounting evidence highlights the role of miRNAs in malignant hematopoiesis via the regulation of oncogenes and tumor suppressors involved in proliferation, differentiation, and cell death. In this review, we provide current knowledge about dysregulated miRNA expression in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 207 publications
(209 reference statements)
0
3
0
Order By: Relevance
“… Schematic representative mechanism of action of the miRNAs studied in this review. Inspired by Sevcikova’s group [ 61 ]. The works studied in this review have highlighted that the miRNAs involved in aGVHD (green box) and cGVHD (red box) could be the biomarkers involving the NF-kB, INF- α/γ, and TNF-α pathways, which increase the levels of oxidative stress and cause apoptosis of cells in the target organs of aGVHD, and some of cGVHD.…”
Section: Discussionmentioning
confidence: 99%
“… Schematic representative mechanism of action of the miRNAs studied in this review. Inspired by Sevcikova’s group [ 61 ]. The works studied in this review have highlighted that the miRNAs involved in aGVHD (green box) and cGVHD (red box) could be the biomarkers involving the NF-kB, INF- α/γ, and TNF-α pathways, which increase the levels of oxidative stress and cause apoptosis of cells in the target organs of aGVHD, and some of cGVHD.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, these molecules could also have an essential function in cold ischemia-reperfusion injury, as previously reported [67,68]. Additionally, since their discovery, research on miRNA expression profiles has shown promise for predicting kidney graft status in a variety of clinical contexts, including acute or delayed graft function, rejection, liver and heart transplant, hematological transplantation, or bone fragility in chronic kidney disease [6,26,[69][70][71][72][73][74][75].…”
Section: Microrna Molecules and Their Role In Transplantationmentioning
confidence: 80%
“…A three-microRNA acute rejection signature, composed of hsa-miR-21-5p, hsa-miR-31-5p, and hsa-miR-4532, could discriminate recipients suffering acute rejection. Other authors also provide a summary of information about the therapeutic relevance of aberrant miRNA expression profiles in hematologic cancer patients and their relationships with various antagomiRs, mimetics, and circular RNAs (circRNAs), as well as with diagnosis, prognosis, and therapy response monitoring [70]. A narrative review written by a different group also examined whether miRNAs could aid in treating osteoporosis and renal osteodystrophy [26].…”
Section: Microrna Molecules and Their Role In Transplantationmentioning
confidence: 99%
“…The focus on serum miRNAs stems from the clinical availability, reliability, and ease of introducing blood-based biomarker tests to clinical practice. Serum miRNAs, released into circulation by various cell types, including hematopoietic and non-hematopoietic cells, would thus provide a more comprehensive insight into the incipient complications and outcome predictions [49][50][51]. In addition, assessment of miR-122 in other populations, including allogeneic hematopoietic stem cell transplant recipients, would be exciting in the context of hepatic GvHD, as miR-122 was already reported to be up-regulated in sera of patients with chronic GvHD [52].…”
Section: Discussionmentioning
confidence: 99%